A salvaguarda do moderno: contribuições para a análise das restaurações de edifícios verticais da área central do Rio de Janeiro - Karine de Arimatéia (2014)
The paper analyses the architectural restoration of vertical constructions that represent modern Brazilian architecture. The purpose is to investigate whether the trend adopted in Brazil for intervention in building restoration follows that adopted most frequently in other countries, distancing intervention from the traditional field of restoration by preserving the image rather than material aspect. The object of study is a set of buildings located in downtown Rio de Janeiro that dominated the city center from the 1930´s to the 1960´s and have undergone several restoration processes led by governmental preservation agencies. The path chosen to analyze the restoration methods used focuses on records of the architectural interventions performed on the Gustavo Capanema Palace, as well as the ABI - Brazilian Press Association headquarters. The processes are on file at the Noronha Santos Archive and the National Historic and Artistic Heritage Institute (IPHAN) in Rio de Janeiro. Research revealed several problems that hindered conclusion of the primary objective, but identified important points regarding interventions in architectural heritage